Sex-Dependent Disposition of Acetaminophen Sulfate and Glucuronide in the in Situ Perfused Mouse Liver - Lee, Jin Kyung (American Society for Pharmacology and Experimental Therapeutics, 2009)
Breast cancer resistance protein (BCRP, ABCG2) is expressed in the hepatic canalicular membrane and mediates biliary excretion of xenobiotics including sulfate and glucuronide metabolites of some compounds. Hepatic Bcrp expression is sex-dependent, with higher expression in male mice. The hypothesis that sex-dependent Bcrp expression influences the hepatobiliary disposition of phase II metabolites was tested in the present study using acetaminophen (APAP) and the generated APAP glucuronide (AG) and sulfate (AS) metabolites in single-pass in situ perfused livers from male and female wild-type and Abcg(–/–) (Bcrp-deficient) mice. Pharmacokinetic modeling was used to estimate parameters governing the hepatobiliary disposition of APAP, AG, and AS. In wild-type mice, the biliary excretion rate constant was 2.5- and 7-fold higher in males than in females for AS and AG, respectively, reflecting male-predominant Bcrp expression. Sex-dependent differences in AG biliary excretion were not observed in Bcrp-deficient mice, and AS biliary excretion was negligible. Interestingly, sex-dependent basolateral excretion of AG (higher in males) and AS (higher in females) was noted in wild-type mice with a similar trend in Bcrp-deficient mouse livers, reflecting an increased rate constant for AG formation in male and AS formation in female mouse livers. In addition, the rate constant for AS basolateral excretion was increased significantly in female mouse livers compared with that in male mouse livers. It is interesting to note that multidrug resistance-associated protein 4 was higher in female than in male mouse livers. In conclusion, sex-dependent differences in conjugation and transporter expression result in profound differences in the hepatobiliary disposition of AG and AS in male and female mouse livers.